2012
DOI: 10.1111/j.1399-6576.2012.02748.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus abrogates the cardioprotection of sufentanil against ischaemia/reperfusion injury by altering glycogen synthase kinase‐3β

Abstract: Sufentanil treatment was ineffective in preventing against ischaemia/reperfusion in diabetic rats, which is associated with the activation of GSK-3β. Our results also suggest that direct inhibition of GSK-3β may provide a strategy to protect diabetic hearts against ischaemia/reperfusion injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 32 publications
(47 reference statements)
0
24
0
Order By: Relevance
“…The above of studies are consistent with this airticle, all confirmed that sufentanil postconditioning can relieve myocardial ischemia-reperfusion injury, even put forward the protection mechanism. But, there a study deems that diabetes mellitus abrogates the cardioprotection of sufentanil against ischemia/reperfusion injury by altering glycogen synthasekinase-3b [9].…”
Section: Discussionmentioning
confidence: 99%
“…The above of studies are consistent with this airticle, all confirmed that sufentanil postconditioning can relieve myocardial ischemia-reperfusion injury, even put forward the protection mechanism. But, there a study deems that diabetes mellitus abrogates the cardioprotection of sufentanil against ischemia/reperfusion injury by altering glycogen synthasekinase-3b [9].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has become a very important target which is able to restore the conditioning cardioprotection by inhibiting the GSK3β activation in diabetic hearts. Two studies have shown diabetes abolished erythropoietin (EPO) or sufentanil-induced cardioprotection against IRI, while it was restored by the administration of GSK3β inhibitor SB216763 (45,46).…”
Section: Hyperglycemia and Diabetesmentioning
confidence: 99%
“…However, in diabetic condition, the cardiac protection of remifentanil preconditioning against IRI was mitigated, which might be associated with reduced recovery of the activities of proteins involved in antiapoptotic pathways including ERK1/2 [13]. Sufentanil is widely used in clinical anaesthesia because of its protective effects against myocardial IRI, but it was ineffective in preventing against IRI in diabetic rats, which is associated with the activation of GSK-3β [12]. Further, the selective κ-OR agonist significantly reduced the myocardial infarct size and increased the expression of stress-inducible heat-shock protein 70 in normal rats, but its effects were abolished in streptozotocin-induced diabetic rats which might be restored by insulin replacement [31].…”
Section: The Challenge Of Opioid-induced Cardioprotection In Diabetesmentioning
confidence: 99%
“…It is of note that myocardial conditioning such as preconditioning mediated cardioprotection could be blocked by opioid receptor antagonists [11] and mimicked by opioid receptor agonists, indicating the involvement of activation of opioid receptor signaling pathways in myocardial IRI protection . Unfortunately, this opioidinduced cardioprotection is abolished or compromised under pathological conditions such as diabetes [12,13]. This review intends to help understand the role of opioid-induced cardioprotection against IRI and the challenges of limiting myocardial IRI in the diabetic hearts.…”
Section: Introductionmentioning
confidence: 99%